Developing Magic Word Puzzle Media for the Development of Polite Language in Children Aged 5-6 Years - Imas Fitrasari; Azi Matur Rahmi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
The ability to use polite language is an important aspect in the social and communication development of early childhood. However, observations at a kindergarten in East Cikarang District indicate that children aged 5–6 years are still not accustomed to using polite expressions such as “please,” “sorry,” “excuse me,” and “thank you” in daily interactions. This study aims to develop the Magic Word Puzzle media as an innovative learning medium to improve the polite language skills of children aged 5–6 years. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The development process was carried out through media design, validation by material experts and media experts, and trial use of the media in early childhood. The results showed that the Magic Word Puzzle media received a very good rating from material experts and media experts, so it was declared suitable for use in learning. This media is designed interactively through puzzle-assembling activities integrated with the introduction and use of polite expressions in various daily situations. The novelty of this research lies in the development of educational puzzle media specifically focused on stimulating children’s polite language skills. Thus, the Magic Word Puzzle media is declared suitable and has the potential to be effective as an alternative learning media in developing polite language skills in children aged 5-6 years.